A comparative analysis of the intermediary systems in South Africa, Namibia, Zimbabwe and Ethiopia - Wilkerson, Tendai Marowa (Rhodes University, Faculty of Law, Law, 2011)
Prior to 1990, very few countries in the world offered special protection to child witnesses interfacing with the justice system. There were no legal provisions permitting testimonial accommodations for children in court. The courtroom experience was significantly traumatic for the children. With the international focus shifting from protecting and upholding the rights of the accused in the courtroom towards a more victim-centred approach, various international and regional instruments have strongly dvocated that children deserve special protection because of their vulnerability. In order for the courts to be able to elicit accurate evidence from the child without further traumatizing the child, research has shown that the child needs assistance. An intermediary may be defined as a person who facilitates communication between the child and the courtroom in a manner that takes into account the child"Ÿs cognitive and developmental limitations. The thesis was prompted by the need to make a contribution to the currently limited body of literature on the intermediary systems in South Africa, Namibia, Zimbabwe and Ethiopia by investigating how the systems can be improved and sustained in a way that helps to protect the child witness in court. Despite the problems the South African courts have had in identifying the appropriate interpretation of its intermediary legislation, the country emerges as a clear leader for the steps it took by creating a positive legal framework within which child protection issues are addressed and introducing the concept of the intermediary. This concept proved to be an inspiration to its neighbours, Namibia and Zimbabwe. The influence of the South African intermediary legislation is evident in the Namibian and Zimbabwean legislation. Although Namibian legislators have drafted laws that permit intermediary assistance in court, there are as yet no intermediaries appointed. In Ethiopia, although there is no discernible intermediary legislation, the country has managed to establish an intermediary system. As a result of the analysis conducted, it is evident that the efficacy of the intermediary system is dependent on the presence of an enabling legislation, its clarity and ease of interpretation, the sensitisation of court role players on child vulnerabilities, the significance of intermediary assistance, and finally a government's commitment towards the implementation process.
Keywords: Juvenile courts -- South Africa; Juvenile courts -- Namibia; Juveline courts -- Zimbabwe; Juvenile courts -- Ethiopia; Children -- Legal status, laws, etc. -- South Africa; Children -- Legal status, laws, etc. -- Namibia; Children -- Legal status, laws, etc. -- Zimbabwe; Children -- Legal status, laws, etc. -- Ethiopia; Child witnesses -- South Africa; Child witnesses -- Namibia; Child witnesses -- Zimbabwe; Child witnesses -- Ethiopia; Mediation -- Law and legislation -- South Africa; Mediation -- Law and legislation -- Namibia; Mediation -- Law and legislation -- Zimbabwe; Mediation -- Law and legislation -- Ethiopia; Children's rights -- South Africa; Children's rights -- Namibia; Children's rights -- Zimbabwe; Children's rights -- Ethiopia